Konsep Kesetaraan Gender Perspektif Fatima Mernissi dan Implikasinya dalam Pendidikan Islam - Afif, Nur; Ubaidillah, Asep; Sulhan, Muhammad (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2020)
Writing this paper aims for every human being to receive equal, fair and equitable treatment in their daily life in any aspect, especially in the world of education. And also to remove the patriarchal ideology which requires the position of men over women. In this research, the writer uses descriptive qualitative method, in which the writer tries to describe what is related to the title of this thesis. The results of this study can be concluded that Fatima Mernissi views that education is an early stage in Islamic education. Where parents act as the first teachers at home. Learning materials as well as knowledge of religion, culture and social customs. In this case, Fatima explained that between women and men, both of them are educators and students, they all have the same learning opportunities because they have the same responsibility. This has happened at the time of the Prophet, he did not divide his people just because of religious and mundane issues, such as social and individual matters. Fatima views that the problem of differences between men and women will continue to exist but within the limits of reasonableness and without eliminating the aspects of human rights inherent in her, as well as the responsibility for individual and social human rights.